PENGARUHOPM,ROE DANROA TERHADAP PERUBAHAN LABA PADA PERUSAHAAN TELEKOMUNIKASI DI BURSA EFEK INDONESIA - Syamni, Ghazali; fe, martunis (JURNAL KEBANGSAAN, 2013)
The purpose of this study was to examine the effect of operating profit margin, return on equity and return on assets to changes in earnings in telecommunications companies in Indonesia Stock Exchange. The data used in this study is a secondary data from financial statements on six telecommunications companies in Indonesia Stock Exchange. Method of data analysis used in this study is multiple regression models. The study found that simultaneous operating profit margin, return on equity and return on assets influence the change in earnings in telecommunications companies in Indonesia Stock Exchange. The same findings were also found partial test results. This indicates that the operating profit margin, return on equity and return on assets is a variable for investors to consider before making a decision to invest. Keywords: operating profit margin, return on equity and return on asset